Perlindungan Hukum terhadap Pihak Debitur dalam Perjanjian Fintech (Financial Technology) - Habibi, Habibi; Rosmidah, Rosmidah; Qodri, M. Amin (Universitas Batanghari Jambi, 2024)
Legal protection for debtors who use standard clauses in fintech (Financial Technology) agreements and legal certainty for fintech (Financial Technology) debtors. This research is a normative research. The research approach is legislation, conceptual, case. The research method used in this study is using a legal sociology approach with an activity plan carried out in this study for 8 months. The materials used in this study are primary legal materials and secondary legal materials and use data collection techniques used in the form of inventory, systematization and interpretation which are descriptive analysis. The results of the study indicate that the issuance of Law Number 21 of 2011 concerning the financial services authority marks the significant development of legal protection for debtors. Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions in Article 18 paragraph (1) determines that Electronic Transactions are stated in an Electronic Contract that binds debtors in an agreement. So that with the existence of a binding contract, there are legal consequences for the debtors, where the debtors have rights and obligations which if violated or not fulfilled, legal action can be taken in the form of filing a lawsuit either in court or outside the court.